1984
DOI: 10.1002/path.1711420308
|View full text |Cite
|
Sign up to set email alerts
|

The glomerular tip lesion: A previously undescribed type of segmental glomerular abnormality

Abstract: We describe a distinctive and previously undescribed abnormality of the kidney. It consists of a combination of changes in the glomerulus and in the proximal convoluted tubule. The glomerular abnormality consists of a well-localized collection of intracapillary foam cells and marked vacuolation of the adjacent glomerular epithelial cells. The abnormality is always situated in the same position in the glomerular tuft namely adjacent to the origin of the proximal convoluted tubule, with adhesion to Bowman's caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 11 publications
6
33
0
4
Order By: Relevance
“…This variant is marked by a segmental lesion at the tubular pole, adjacent to the origin of the proximal tubule. The biopsy specimen in this case fits the original description of the GTL, which reported that the remaining glomeruli show no alterations except for diffuse podocyte effacement on electron microscopy, akin to the findings of minimal-change disease (5). The Columbia classification of FSGS uses less restrictive criteria and defines the tip variant as having the presence of at least one tip lesion in the absence of collapsing lesions or perihilar sclerosis (6).…”
Section: Question 2asupporting
confidence: 71%
“…This variant is marked by a segmental lesion at the tubular pole, adjacent to the origin of the proximal tubule. The biopsy specimen in this case fits the original description of the GTL, which reported that the remaining glomeruli show no alterations except for diffuse podocyte effacement on electron microscopy, akin to the findings of minimal-change disease (5). The Columbia classification of FSGS uses less restrictive criteria and defines the tip variant as having the presence of at least one tip lesion in the absence of collapsing lesions or perihilar sclerosis (6).…”
Section: Question 2asupporting
confidence: 71%
“…18 Several reports in the past have shown an excellent response to steroid therapy in the tip variant with outcomes similar to the minimal change disease rather than FSGS. [12][13][14][15]24 However, it has also been shown that the overall behavior and ultimate outcome of this disease are more like FSGS as was seen in our study also. 9,[20][21][22] The incidence of initial steroid responsiveness was higher in the tip variant with 72% of patients achieving complete remission after steroid therapy.…”
Section: Discussionsupporting
confidence: 73%
“…7 It has been postulated that this lesion is the response of the glomeruli to heavy proteinuria and cases with this subtype of FSGS with no other lesion on histopathology may actually represent a form of minimal change disease (MCN). [12][13][14] However, there have been various studies which have shown that despite the histopathological similarities to the benign MCN the clinical course of the disease is similar to that of primary FSGS. 9,15,16 Hence with the aim to study the clinical and histopathological features and the natural history and response to therapy of this variant of FSGS, we retrospectively reviewed our cases of primary FSGS and the tip lesion variant and compared the clinical and biochemical parameters as well as outcome of these patients with those of a relatively common histological variant of NOS.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports in nephrotic patients with the tip lesion suggested an excellent response to steroids and favorable course similar to that of minimal-change disease rather than FSGS (14,21,23,24). Subsequent reports found that the response and course in patients with the tip lesion was similar to that of patients with FSGS and thus questioned the clinical significance of this feature (6,10,25,26).…”
Section: Discussionmentioning
confidence: 99%